FASILITAS PENUNJANG PENERANGAN JALAN DI WILAYAH RT 04 RW 02 KELURAHAN PEDALANGAN KECAMATAN BANYUMANIK KOTA SEMARANG: SEBUAH USULAN DESAIN TIANG LAMPU - Ratih Widiastuti (Jurnal Pengabdian Vokasi, 2022)
The authority of the area of RT 04 RW 02, Pedalangan region, Banyumanik District, Semarang City has ambition to provide adequate infrastructures to support the daily activities of their people. Several areas are identified as yards do not have adequate street lighting. To date, the street lightings are only infront of houses. In order to support the agenda of the authority and also practices the knowledge from the university through the Community Service program, a recommendation design for street lamp pole was proposed.